2012
DOI: 10.3126/nje.v2i3.6902
|View full text |Cite
|
Sign up to set email alerts
|

Study of Risk factors of Coronary Heart Disease in Urban Slums of Patna

Abstract: Background Coronary Heart Diseases (CHDs) are imminent cause of disability and death with economic adverse effects in the disadvantaged population in India. Materials and Methods This population based study was conducted from 1st December 2010 till 31st May 2011 among the adults in the slums of Patna to assess the magnitude and risk factors of CHDs concerning age, sex, tobacco use, alcohol consumption, physical activity, weight, height, waist circumference, blood pressure and random capillary blood glucose (R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(35 citation statements)
references
References 16 publications
2
29
4
Order By: Relevance
“…Consistent results have been reported in number of studies, conducted among urban poor, across the globe (16)(17)(18). The finding also went in line with the Nepalese study featuring Sinamangal slum of Kathmandu Valley (10).…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Consistent results have been reported in number of studies, conducted among urban poor, across the globe (16)(17)(18). The finding also went in line with the Nepalese study featuring Sinamangal slum of Kathmandu Valley (10).…”
Section: Discussionsupporting
confidence: 73%
“…Almost all studies among different segments of the population of Nepal showed consistent result, with limited share of women in drinking (11)(12)(13)(14). An increasing body of literature in developing countries showed consistent gender differences in drinking of the urban poor (10,(15)(16)(17)(18)(19). Gender difference related data on drinking of urban poor's is scarce in Nepal.…”
Section: Introductionmentioning
confidence: 99%
“…But compared to the urban poor from Kerala, India, there is not a large difference (37.3%) [25]. By gender-wise stratification also, more men and women in our study smoke compared to the of the Nepal's national data (31.2% and 15.5%) [19], the urban population of Myanmar (44.8 and 7.8%) [22], and the urban slum of Patna (21.15% and 5.91%) [24]. Comparatively, fewer women (12.2%) and more men (62.6%) in the Kerala slum smoked [25].…”
Section: Tobacco Consumptionmentioning
confidence: 43%
“…Prevalences of alcohol consumption in the males and females of the study area were higher than the national averages for men (39.3%) and women (16.5%) [19]. Among males, the current drinking rate is higher than that in their counterparts from Patna (16.65%) [24] and Kerala (45.4%) [25]. The highest prevalence of current drinking was seen in the 35-44 years age group (72.1%).…”
Section: Alcohol Consumptionmentioning
confidence: 88%
See 1 more Smart Citation